Oral health knowledge and practice among pupils in a private school : a basis for an intervention program - Fadare, Stephen Ayoada (City of San Fernando City, La Union : [s.n.], 2018)
This descriptive study identified and analyzed the oral health knowledge and practice among private school pupils. Specifically, it looked into the profile of respondents along grade level, sex and highest educational attainment of their parents, knowledge on causes and preventive measures of oral diseases, strengths and weaknesses of oral health and extent of practice on oral hygiene and extent of practice along oral hygiene, correlation analysis between their level of knowledge on oral health and extent of practice on oral hygiene.
Bibliography: pages 77-83.
CHED-La Union
Keywords: Dentistry